Pengaruh Guru Dalam Pemberian Penguatan (Reinforcement) Terhadap Aktivitas dan Kreativitas Belajar Siswa Kelas IV MIN Kota Cirebon - Jazilah, Rofiatul; Udin, Tamsik; Maufur, Syibli (Indonesian Journal of Elementary Education (IJEE), 2022)
AbstrakPenelitian ini dilatarbelakangi oleh kurangnya aktivitas dan kreativitas siswa dalam proses pembelajaran. Hal ini terlihat dari perilaku siswa yang kurang bersemangat dan mudah bosan ketika belajar, serta kesulitan untuk membuat kesimpulan dalam pembelajaran. Penelitian ini bertujuan untuk mendeskripsikan pengaruh guru dalam pemberian penguatan (reinforcement) terhadap aktivitas belajar siswa kelas IV MN Kota Cirebon serta mendeskripsikan pengaruh guru dalam pemberian penguatan (reinforcement) terhadap kreativitas belajar siswa kelas IV MIN Kota Cirebon. Pendekatan yang digunakan adalah kuantitatif dengan metode penelitian ex post facto. Pengumpulan data melalui observasi, penyebaran angket dan dokumentasi. Populasi sebanyak 43 siswa kelas IV MIN Kota Cirebon dan teknik pengambilan sampel yaitu teknik sampling jenuh. Analisis data yang digunakan adalah uji normalitas, uji linearitas, uji regresi linear sederhana dan uji hipotesis. 1) Hasil observasi pelaksanaan pemberian penguatan (reinforcement) adalah 78,31% dengan kriteria baik. 2) Hasil lembar angket aktivitas belajar adalah 82,16% dengan kriteria baik. 3) Hasil lembar angket kreativitas belajar adalah 74,94% dengan kriteria cukup baik. 4) Hasil uji regresi linear sederhana didapatkan ada pengaruh pemberian penguatan (reinforcement) terhadap aktivitas belajar siswa sebesar 66,1%. 5) Hasil uji regresi linear sederhana didapatkan ada pengaruh pemberian penguatan (reinforcement) terhadap kreativitas belajar siswa sebesar 59,5 %.Kata Kunci: Pemberian Penguatan (Reinforcement), Aktivitas Belajar, Kreativitas BelajarAbstractThis research is motivated by the lack of activity and creativity of students in the learning process.  This can be seen from the behavior of students who are less enthusiastic and easily bored when studying, students are reluctant to read books to answer the practice questions that the teacher gives, do not listen to the teacher's or friend's explanation who are presenting, less participating in experimental activities, and difficult to remember teaching material that has been  delivered by the teacher.  They tend to prefer chatting with their classmates or playing alone when the learning process takes place.  As for when the teacher finishes explaining the material and asks about material that is not yet understood, only two to three students sometimes ask questions.  In addition, students are rarely able to provide ideas / ideas when the teacher presents a problem, students cannot complete the task of the teacher quickly, as well as difficulty in making conclusions in learning.  The research conducted by this researcher aims to describe the influence of the teacher in giving reinforcement to the learning activities of class IV MIN Cirebon students and to describe the influence of the teacher in providing reinforcement to the learning creativity of class IV MIN Cirebon students.  This research uses a quantitative approach with ex post facto research methods.  Data collection was carried out through observation, questionnaire and documentation distribution.  The population was 43 students in class IV MIN of Cirebon City and the sampling technique used was saturated sampling technique.  The data analysis used is the normality test, linearity test, simple linear regression test and hypothesis test.  1) The recapitulation results of the observation that the implementation of giving reinforcement (reinforcement) is 78.31% with good criteria.  2) The recapitulation results of the learning activity questionnaire sheet was 82.16% with good criteria.  3) The recapitulation results of the learning creativity questionnaire were 74.94% with quite good criteria.  4) The results of a simple linear regression test the effect of giving reinforcement to student learning activities obtained a significance value of 0.001.  Because according to the hypothesis the significance value is smaller than 0.05 then Ho is rejected, meaning that there is an effect of giving reinforcement (reinforcement) on student learning activities.  The effect is 66.1%.  5) The results of a simple linear regression test the effect of giving reinforcement to student learning creativity obtained a significance value of 0.001.  Because according to the hypothesis the significance value is less than 0.05 then Ho is rejected, meaning that there is an effect of giving reinforcement to student creativity.  The effect is 59.5%.Keywords: Giving Reinforcement, Learning Activities, Learning Creativity.